The Influence of Technology Readiness, Personalized Learning Experience and Digital Learning Continuance Intention on Technology-Enhanced Learning Performance - Muhamad Risal Tawil; Desty Endrawati Subroto; Haris Karyadi; Joni Wilson Sitopu; Agus Rofi'i; Firman Aziz (Journal of Information System, Technology and Engineering, 2026)
The rapid development of technology has transformed the way we learn, making Technology-Enhanced Learning Performance of utmost importance to educators, schools, and policy makers. This research aims to investigate the influence of Technology Readiness, Personalized Learning Experience and Digital Learning Continuance Intention on Technology-Enhanced Learning Performance among college and university students. For our study design we gathered data from students and analyzed it using Multiple Linear Regression. We showed the validity of the records the use of the t-check method in advance than inspecting the information and the reliability using Cronbachs Alpha. The findings determined out that era Readiness, personalised getting to know enjoy and virtual mastering Continuance goal all had an effect on technology-extra fine getting to know universal performance. Personalised mastering revel in changed into the most widespread element followed through the use of technology Readiness and virtual gaining knowledge of Continuance goal. Because of this faculties need to prepare university students to make use of era to assemble mastering environments which can be personalized to every college student’s requirement and to have interaction college students within the gaining knowledge of approach. This can help students carry out their wonderful in generation based totally completely topics. This research type of offers a higher know-how of the manner top notch factors come collectively, to beautify learning results, within the age we are in. It additionally offers a course to schools and technology companies, like what to do for you to improve studying within the digital generation, not most effective in principle but in sensible terms, sure.